Critical overview of biorefinery approaches for valorization of protein rich tree nut oil industry by-product. (October 2022) - Sari, T.P.; Sirohi, Ranjna; Krishania, Meena; Bhoj, Suvarna; Samtiya, Mrinal; Duggal, Muskaan; Kumar, Deepak; Badgujar, Prarabdh C.
Graphical abstract: Highlights: De-oiled cakes from tree nuts-valorization by enzymatic hydrolysis & fermentation possible. Enzymatic hydrolysis of these cakes far better technique than microbial fermentation. Treenut deoiled cakes derived bioactive peptide: applications in food & therapeutics. Safety & efficacy evaluation of novel peptides with bioactivity be studied in vivo. Masking bitter taste, sensory profiling needed for functional food applications. Abstract: This review explores reutilization opportunities of protein-rich bio-waste derived from the major tree nuts (almonds, walnuts, and cashew nuts) oil processing industries through biorefinery strategies. The mechanically pressed out oil cakes of these nuts have high protein (45–55%), carbohydrate (30–35%), and fiber that could be utilized to produce bioactive peptides, biofuels, and dietary fiber, respectively; all of which can fetch substantially greater value than its current utilization as a cattle feed. Specific attention has been given to the production, characterization, and application of nut-based de-oiled cake hydrolysates for therapeutic benefits including antioxidant, antihypertensive and neuroprotective properties. The often-neglected safety/toxicological evaluation of the hydrolysates/peptide sequences has also been described. Based on the available data, it is concluded that enzymatic hydrolysis is a preferred method than microbial fermentation for the value addition of de-oiled tree nut cakes. Further, critical insights on the existing literature as well as potential research ideas have also been proposed.